Pengembangan Buku Referensi Bioetika Jurusan Pendidikan IPA Biologi IAIN Mataram - Muh. Zaini Hasanul Muttaqin; Mohamad Amin; Siti Zubaidah (Universitas Islam Negeri Mataram, 2016)
The purpose of this research is to produce a bioethics reference book on biological science department of Islamic State Institute of Mataram. This research used a model of development proposed by Borg and Gall (1983). The results of this research are: 1) the limitation level of biological science education department student of Islamic State Institute of Mataram to the bioethics reference book is needed, 2) the trial results show that the reference book reference book is very valid.